2018
DOI: 10.1096/fj.201700736rr
|View full text |Cite
|
Sign up to set email alerts
|

Decreased generation of C‐terminal fragments of ApoER2 and increased reelin expression in Alzheimer's disease

Abstract: Increasing evidence indicates that altered reelin signaling could contribute to synaptic dysfunction in Alzheimer's disease (AD). We found that reelin protein and mRNA levels were increased in the AD brain (particularly at advanced Braak stages in apolipoprotein E4 noncarriers), compared with that of control subjects. The β-amyloid (Aβ) protein impairs reelin activity and increases reelin expression through a mechanism that is not yet understood. To explore that mechanism, we examined the effect of Aβ aa 1-42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 70 publications
3
27
0
Order By: Relevance
“…Specifically, the misprocessing of ApoER2 in CD2AP-depleted cells was rescued with an active form of the Rab5 GTPase ( Figure 2G and H) that is involved in membrane trafficking 59 , or inhibition of g-secretase ( Figure 2J and K) that cleaves ApoER2 to release a C-terminal fragment 60 . Our results on the effects of CD2AP loss function on ApoER2 levels are reminiscent of those showing that ApoE4 also impairs the trafficking of ApoER2 resulting in its degradation 57 ; they are also in agreement with observations that processing of the receptor is disturbed in the cortex of AD patients 61,62 . Last, to determine whether ApoER2 signaling is impaired in the absence of CD2AP, we treated CD2AP-depleted cells with the glycoprotein Reelin, a well characterized ligand for ApoER2, secreted by astrocytes and neurons with protective effects against parenchymal Ab toxicity in animal models of AD 63,64 .…”
Section: No Interaction Was Found Between Cd2ap and Picalm (Phosphatisupporting
confidence: 91%
“…Specifically, the misprocessing of ApoER2 in CD2AP-depleted cells was rescued with an active form of the Rab5 GTPase ( Figure 2G and H) that is involved in membrane trafficking 59 , or inhibition of g-secretase ( Figure 2J and K) that cleaves ApoER2 to release a C-terminal fragment 60 . Our results on the effects of CD2AP loss function on ApoER2 levels are reminiscent of those showing that ApoE4 also impairs the trafficking of ApoER2 resulting in its degradation 57 ; they are also in agreement with observations that processing of the receptor is disturbed in the cortex of AD patients 61,62 . Last, to determine whether ApoER2 signaling is impaired in the absence of CD2AP, we treated CD2AP-depleted cells with the glycoprotein Reelin, a well characterized ligand for ApoER2, secreted by astrocytes and neurons with protective effects against parenchymal Ab toxicity in animal models of AD 63,64 .…”
Section: No Interaction Was Found Between Cd2ap and Picalm (Phosphatisupporting
confidence: 91%
“…Moreover, APOE 4 has been identified as a ligand for the LDL receptors (LDLRs) family and that ApoE receptor 2 (ApoEr2) [266], together with VLDL receptor (VLDLR), have major impacts on brain development and adult synaptic plasticity [267,268]. ApoEr2 acts through the activation of Reelin [269271], whose function could be modulated by specific compounds that secondarily would act or reduce the APOE 4 detrimental effects on the CNS in general, or on dementia being the main genetic risk factor for AD [272,273].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…134,135 Surprisingly, recent studies demonstrated a possible compensatory mechanism that upregulated Reln expression after Aβ-induced disruption of RELN conformation impaired its activity and compromised RELN-ApoER2 signaling. 136,137 However, such a compensatory increase in the RELN level did not appear to be mediated by DNA methylation, as the promoter methylation remained unchanged in both the Aβ-treated neuroblastoma cell line and frontal cortical genomic DNA extracts from AD patients. 136 In view of this finding, it is likely that other epigenetic mechanisms, for example, histone modifications, contribute to the observed elevation of RELN, as histone acetylation was shown to be involved in synaptic plasticity and memory.…”
Section: Neurochemical Processesmentioning
confidence: 95%
“…136,137 However, such a compensatory increase in the RELN level did not appear to be mediated by DNA methylation, as the promoter methylation remained unchanged in both the Aβ-treated neuroblastoma cell line and frontal cortical genomic DNA extracts from AD patients. 136 In view of this finding, it is likely that other epigenetic mechanisms, for example, histone modifications, contribute to the observed elevation of RELN, as histone acetylation was shown to be involved in synaptic plasticity and memory. 138 Besides its interaction with Aβ, RELN was also found to be negatively associated with the progression of NFT pathology.…”
Section: Neurochemical Processesmentioning
confidence: 95%